Design and analysis of impact attenuator for UiTM formula SAE car 2016 / Naziratie Assrinie Assan...[et al.] - Assan, Naziratie Assrinie; Ab Ghani, Amir Radzi; Ramly, Ramzyzan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Formula SAE is an international student design competition which is held in various parts of the world that challenges students to conceive, design, fabricate and test a single seater race car. Teams are evaluated based on business and technical presentations and dynamic performance of their cars. One of the important requirements of the Formula SAE car is its impact attenuator. It must be designed to absorb the specified impact energy. It is placed at the front of the car to protect the driver in the event of frontal collision. A new impact attenuator design which consists of aluminium circular tubes and L-sections arranged in a specified configuration is proposed. The attenuator is subjected to static and impact loads to determine its initial peak force (IPF), crush force efficiency (CFE) and specific energy absorption (SEA). Simulation result for static loading is validated by experiment. Minimum absorbed impact energy of 7350 J with peak acceleration of less than 40g and mean deceleration of 20g as specified in Formula SAE regulations is achieved. Impact simulation result also confirms that the impact attenuator is able to fulfil the requirements.